The Effect of Education Level and Gender on Students’ Metacognitive Skills in Malang, Indonesia - Siswati, Bea Hana; Corebima, Aloysius Duran (Advances in Social Sciences Research Journal, 2017)
The students’ thinking ability will develop with age. Educators are expected to know the development of the students’ thinking ability, so that the empowerment of their thinking abilities, including metacognitive skills, can be done optimally. Gender is believed to be associated with the development of a person’s thinking ability. This quasi experimental research aimed at investigating the effect of level of education and gender on students’ metacognitive skills. The population of this research was the students of junior high schools and senior high schools in malang in 2015/2016 academic year. The school samples used in this research were junior high school muhammadiyah 1 and senior high school muhammadiyah 1 malang. The metacognitive skills were measured by essay test, and assessed by using the rubric of metacognitive skills. The results of the data analysis showed that the education level had an effect on students’ metacognitive skill, but gender as well as the interaction between education level and gender did not have an effect on students’ metacognitive skill. It is recommended to conduct further research related to the effect of education level on metacognitive skill using a bigger number of samples and even involving the samples studying at elementary school level.